RANCANG BANGUN MODUL UKUR TEKANAN PIJAK TELAPAK KAKI ROBOT HUMANOID - Maulana Aziz Assuja; Septina Nainggolan; Saniati Saniati (Jurnal Teknik dan Sistem Komputer, 2023)
Maintaining balance for humanoid robots is one of the core problems to be solved. Krakatau FC as a humanoid type robot performs balancing based on error information obtained from the IMU sensor. Information from the IMU alone is considered inadequate because it ignores the contours of the robot's stepping area which greatly influences the actions that must be taken to maintain balance. The focus of this research is to create a foot pressure measurement module that is compatible with the Dynamixel communication protocol. The sensor used to measure pressure is a Force Sensitive Resistor (FSR) sensor. The test results show the module's ability to measure the pressure exerted by the robot's legs and communicate with the robot's main controller using the Dynamixel protocol. From the test, it is also known that the modules made can help the robot's mechanical calibration process based on the comparison of the pressure between the right and left soles of the feet.